Pemberdayaan Masyarakat Menuju Desa Kasemek Besti (Bebas Sampah dan Stunting) - Anggraini, Risma Devita; Prastika, Sinta Yuli; Ika Putri Maharani, Ika Putri; Devi, Almira Aisha; Putri, Kristin Ampudan Anggi Putri; Ningtyias, Farida Wahyu (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Health problems that often occur in Kasemek Village, Tenggarang Subdistrict, Bondowoso Regency are dengue fever and stunting in toddlers. This is caused by waste problems and lack of knowledge of mothers regarding balanced nutrition. The purpose of this activity is to increase community knowledge related to how to manage waste and prevent stunting in children. Method: This activity partnered with the Kasemek Village Government and the Bondowoso District Environment Office with 40 participants. The methods used were community education and advocacy. Community education was conducted through education with pre-test and post-test. Result: The results achieved from this activity included the availability of waste containers, waste carts, and a management system for temporary shelters (TPS) in Kasemek Village. In addition, educational activities resulted in increased knowledge of mothers regarding balanced nutritious food to fulfill nutrition in toddlers to prevent stunting. Conclusion: Community empowerment activities have made waste disposal facilities more adequate and increased mothers' knowledge of healthy food menus.